Habilitation Of Cerebral Palsy Spastic Type + Upper Respiratory Track Infection + Malnutrition + Respiratory Disturbance + Feeding Problem + Mobilization Disturbances + Communication Disturbance - Dewi Nur Fiana (Fakultas Kedokteran, 2020)
Cerebral Palsy (CP) is a disorder of movement and posture that appear during infancy or early childhood. It is caused by nonprogressive damage to the brain before, during or shortly after birth. CP is not a single disease but a name given to a wide variety of static neuromotor impairment Syndromes occurring. Secondary to a lesion in the developing brain.1 HR, 26 month old boy,was consulted by Pediatric Department on 11-09-2015 with diagnose Epilepsi focal symptomatic + Cerebral Quadriplegi + suspect visupect visual impairment. HR had ad bonam for prognosis quo ad vitam and ad sanationam, but dubia ad bonam for quo ad functionam. He had stable hemodynamic and but have high risk of infection or risk of aspiration right now. His maturation is at brain stem level and her GMFCS level was V. He might have dependence in mobility. Prognosis still dubia because during therapy at physical medicine & rehabilitation department, his body weight was increase, his pulmonary problem is improve, His head and neck control improved, and his ability to rolling is improve. His parents also understand their son condition and set a reasonable expectation.Keywords: Cerebral Palsy ,Feeding Problem, Immobilization, Sapsticity,